DIALEKTIKA TIGA PILAR HUBUNGAN FILSAFAT ISLAM, TEOLOGI DAN TASAWUF - Irwan Setia Budi (EDUTHINK: Jurnal Pemikiran Pendidikan Islam, 2022)
Oftentimes, We hear that Tasawuf, theology, and philosophy of Islam have a historical relationship which was almost discussed by Muslim philosophers because the science of Tasawuf can not be separated from kalam theory and philosophy. All three were closely related. Both tasawuf and kalam theory discussed the truth. Tasawuf theory said that the truth had several ways. In another way, The kalam theory explained that got the truth from Al-Qur’an and Hadist. Kalam theory discussed faith, while the Tasawuf theory discussed ways or methods to feel confidence and trust and, peace, while the relationship between Tasawuf and philosophy was the search for truth. Tasawuf was a spiritual path with mystical truth according to the path and sunnah. Meanwhile, philosophy was not meant only to be rationalistic philosophy with intellectual schools in Islamic culture.